The Changing Landscape of HIS in SA - Shaw, Vincent Paul; Claasen, Elmarie; Brown, Jenni (Journal of Health Informatics in Africa, 2013)
Background and Purpose: South Africa, with support from the University of Oslo, developed the District Health Information Software, version 1.3 between 1996 and 2006, and together with support from the National Department of Health, rolled the system out across the whole country. Between 2006 and 2010, DHISv14 was implemented in the country, and a significant number of data sets were developed to support the national health information system (HIS). South Africa is now preparing for the transition to DHIS2, which is seen as a key component of the information systems that will be required to support the development of the national health insurance system in South Africa. The transition to DHIS2 is different in South Africa because of the long-standing investment in the DHIS14 system, and the multitude of different data sets that have developed to support the National HIS. This paper describes the preparations that are taking place, at organisational level (both within the public sector at national, provincial, district and sub-district levels, as well as amongst NGOs) to develop capacity to support the use of the DHIS2, as well as technical level to ensure an appropriate transition. Methods: The research is set within the multi-country HISP-network action research project. The authors have been involved in the development of the national health information system since 1992, both as public sector employees and as employees to HISP South Africa. The paper draws on the interpretive research tradition for the data analysis, and reflects on processes that have unfolded in the last two years, as part of a larger action research project in which HISP is engaged. Data sources are personal diaries, meeting notes, official documentation and workshop reports. Additional sources of information included in-depth interviews with key informants, informal discussions, as well as field visits and observations. Direct observation of staff at work was a major source of information as authors worked with the country team. Results: The authors use the HMN framework for HIS strengthening to analyse the HIS developments over a 20 year period, and use this to reflect on how the approach that is being adopted to introduce DHIS2 in South Africa will influence previous approaches. The presentation highlights the strategies that are used to overcome technical, organisational and behavioural barriers, and how these relate to the current policy environment in SA. In particular, we reflect on the skills sets that are needed to support DHIS2, and efforts to ensure that these skills are available in a sustainable manner. In response to the technical requirements of the DHIS2, organisational capacity needs to be adjusted, within the public sector as well as within NGOs that support the NDoH. The anticipated improvements to the national health information system are discussed, and the implications of the experiences are highlighted for other countries. Conclusions: Over 20 countries in Sub-Saharan Africa are using the DHIS. In many of these countries, the information systems are still fairly simple, or in the process of being established. In comparison, South Africa has a fairly advanced National HIS, with many facets that can now be managed in a more integrated manner. This paper describes the processes that are being planned to ensure a smooth transition from the distributed access databases used in DHISv14 to the centralised and integrated system represented in DHIS2. Keywords: Information Systems Development, Skills sets for information systems support, Data warehousing, Business intelligence